Syntheses, structures, and stabilities of aliphatic and aromatic fluorous iodine(I) and iodine(III) compounds: the role of iodine Lewis basicity - Mukherjee, Tathagata; Biswas, Soumik; Ehnbom, Andreas; Ghosh, Subrata K.; El-Zoghbi, Ibrahim; Bhuvanesh, Nattamai; Bazzi, Hassan S.; Gladysz, John A. (Beilstein Journal of Organic Chemistry, 2017)
The title molecules are sought in connection with various synthetic applications. The aliphatic fluorous alcohols RfnCH2OH (Rfn = CF3(CF2)n–1; n = 11, 13, 15) are converted to the triflates RfnCH2OTf (Tf2O, pyridine; 22–61%) and then to RfnCH2I (NaI, acetone; 58–69%). Subsequent reactions with NaOCl/HCl give iodine(III) dichlorides RfnCH2ICl2 (n = 11, 13; 33–81%), which slowly evolve Cl2. The ethereal fluorous alcohols CF3CF2CF2O(CF(CF3)CF2O)xCF(CF3)CH2OH (x = 2–5) are similarly converted to triflates and then to iodides, but efforts to generate the corresponding dichlorides fail. Substrates lacking a methylene group, RfnI, are also inert, but additions of TMSCl to bis(trifluoroacetates) RfnI(OCOCF3)2 appear to generate RfnICl2, which rapidly evolve Cl2. The aromatic fluorous iodides 1,3-Rf6C6H4I, 1,4-Rf6C6H4I, and 1,3-Rf10C6H4I are prepared from the corresponding diiodides, copper, and RfnI (110–130 °C, 50–60%), and afford quite stable RfnC6H4ICl2 species upon reaction with NaOCl/HCl (80–89%). Iodinations of 1,3-(Rf6)2C6H4 and 1,3-(Rf8CH2CH2)2C6H4 (NIS or I2/H5IO6) give 1,3,5-(Rf6)2C6H3I and 1,2,4-(Rf8CH2CH2)2C6H3I (77–93%). The former, the crystal structure of which is determined, reacts with Cl2 to give a 75:25 ArICl2/ArI mixture, but partial Cl2 evolution occurs upon work-up. The latter gives the easily isolated dichloride 1,2,4-(Rf8CH2CH2)2C6H3ICl2 (89%). The relative thermodynamic ease of dichlorination of these and other iodine(I) compounds is probed by DFT calculations.
Keywords: chlorination; copper mediated perfluoroalkylation; crystal structure; DFT calculations; fluorous; hypervalent iodine; nucleophilic substitution; polar space group